Novel Earthworm-Based Halal Fish Feed - Z. Zakaria (Universiti Sains Islam Malaysia, 2024)
There is a need in aquaculture industries for halal feed. The Malaysian National Fatwa Council Committee has stated that Muslim is forbidden from consuming fish that has been fed with non-halal food. However, most of the imported fish feeds are made from non-halal resources such as waste from pig abattoir. Consequently, this research focuses on utilizing halal source for fish feed formulation which is the earthworm powder. By selecting earthworm powder as the main ingredient in the fish feed formulation. this abides with the rule as suggested by the Fatwa Council. A verification experiment has been conducted on the earthworm powder to determine the protein and lipid content. Protein analysis using the Kjeldhal method has showed that earthworm powder contain high protein up to 72% dry matter and this is comply with general quality standard of protein which is > 68%. Extraction of lipid also revealed that there was &12% (wtw) of lipid. Formulation of fish feed using 50% of earthworm powder with combination of coconut dregs and soybean meal and rice bran was found contain adequate nutritional value and comparable to the existing fish feed.